2008
DOI: 10.1017/s0266467408005075
|View full text |Cite
|
Sign up to set email alerts
|

Above-ground biomass and productivity in a rain forest of eastern South America

Abstract: Abstract:The dynamics of tropical forest woody plants was studied at the Nouragues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
101
4
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(117 citation statements)
references
References 58 publications
7
101
4
5
Order By: Relevance
“…The first modified parameter value is f alloc,leaf which is slightly increased from 0.27 to 0.30, supported by NPP leaf estimates reported by Chave et al (2008) for Nouragues in central French Guiana and by the findings of Malhi et al (2011) for 35 sites in tropical evergreen forests worldwide. The latter reported a fraction of 0.41 NPP tot allocated to the entire canopy (leaves, flowers, fruits and fine twigs) that, assuming that the percentage of leaves is 73 % (Malhi et al, 2011), results in an f alloc,leaf value of 0.3.…”
supporting
confidence: 59%
“…The first modified parameter value is f alloc,leaf which is slightly increased from 0.27 to 0.30, supported by NPP leaf estimates reported by Chave et al (2008) for Nouragues in central French Guiana and by the findings of Malhi et al (2011) for 35 sites in tropical evergreen forests worldwide. The latter reported a fraction of 0.41 NPP tot allocated to the entire canopy (leaves, flowers, fruits and fine twigs) that, assuming that the percentage of leaves is 73 % (Malhi et al, 2011), results in an f alloc,leaf value of 0.3.…”
supporting
confidence: 59%
“…Despite this requirement, most of the past studies in tropical forests are found to be limited to analyzing the aboveground systems (Chave et al 2008;Djomo et al 2011;Malhi et al 2011;Doughty et al 2013;Ngo et al 2013;Girardin et al 2014;Malhi et al 2014) and only a few studies concern to the belowground aspects (Ibrahima et al 2010;Powers and Perez-Aviles 2013;Noguchi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Lianas and trees are the two dominant plant growth forms in tropical forests, and there is a growing body of evidence suggesting that lianas are increasing relative to trees in Neotropical forests (Phillips et al 2002, Benı´tez-Malvido and Martı´nez-Ramos 2003, S. J. Wright et al 2004, Chave et al 2008, Foster et al 2008, Schnitzer and Bongers 2011, Yorke et al 2013, Schnitzer 2015. We are not sure why.…”
Section: Introductionmentioning
confidence: 99%